Determinants and performance outcome of manufacturing SMEs use of internet-based IOISs to share inventory information. (29th November 2010) - Hadaya, Pierre; Pellerin, Robert
This identifies the determinants and performance outcome of internet-based Interorganisational Information Systems (IOISs) to share inventory information with their key customers. The proposed model is tested on data collected from 240 senior managers of Canadian SMEs. Results indicate that: both determinants related to the technology and those related to business relationships affect SME's use of internet-based IOISs; the use of IOISs to share inventory information positively impacts manufacturing SMEs' operational performance; under greater use of internet-based IOISs to support transactions, an increase in the use of internet-based IOISs to share inventory information does not lead to an increase in performance.